Evaluasi Kesiapan Penerapan Rekam Medis Elektronik di Tingkat Puskesmas, Kota Gorontalo - Basri Umar; Rosdiana Kaharu; Maimun I. Bilondatu; Aida Muhdar (HB PRESS, 2026)
Electronic Medical Records (EMR) play an important role in improving the quality and efficiency of health services at Community Health Centers (Puskesmas). However, several Puskesmas in regional areas are still not fully prepared to implement EMR systems. This study aimed to evaluate the readiness of Puskesmas in Gorontalo City for the implementation of Electronic Medical Records. A quantitative descriptive approach was used in this study. Data were collected using a multiple-choice questionnaire that measured readiness in terms of infrastructure, human resources, organizational culture, governance, and leadership. The study involved all Puskesmas in Gorontalo City, consisting of 10 Puskesmas, namely Puskesmas Kota Utara, Dumbo Raya, Sipatana, Kota Timur, Hulonthalangi, Pilolodaa, Kota, Kota Selatan, and Kota Barat, with a total of 136 respondents participating in the survey. The results showed that the Puskesmas in Gorontalo City were generally ready to implement EMR systems. Organizational culture achieved a readiness score of 89.7%, governance and leadership scored 94.9%, and human resources also scored 94.9%. However, infrastructure readiness was still relatively low, with a score of 59.5%, indicating that improvements in technological facilities and supporting infrastructure are still required before full EMR implementation can be achieved. In conclusion, most aspects of EMR readiness among Puskesmas in Gorontalo City are categorized as ready, except for infrastructure, which remains a major challenge for successful implementation.